B7-1 (CD80) and B7-2 (CD 86) expression in human tubular epithelial cells in vivo and in vitro - Niemann-Masanek, Ulrike; Müller, Alexander; Yard, Benito A.; Waldherr, Rüdiger; Woude, Fokko J. van der (Nephron, 2002)
BACKGROUND: Tubulointerstitial inflammation with infiltration of mononuclear cells plays an important role in acute allograft rejection and in the progression of renal diseases. We therefore investigated in vivo the expression of the costimulatory molecules B7-1 and B7-2 on proximal tubular epithelial cells (PTEC) under normal and pathologic conditions and analyzed the regulation and functional role of these molecules after cytokine and CD40 activation in vitro. METHODS: Immunohistological staining for B7-1 and B7-2 on cryostat sections of core needle biopsies from patients with different renal diseases was examined. Patients were divided into three groups: group A: diffuse interstitial inflammation; group B: minor interstitial inflammation; group C: no interstitial inflammation. In addition, the expression of B7-1 and B7-2 protein and mRNA of cultured PTEC that had been stimulated with cytokine-combinations in absence or presence of a stimulatory anti-CD40 antibody was investigated by means of FACS analysis and RT-PCR. The functional role was analyzed in MKLCs with cytokine and anti-CD40 prestimulated PTEC by measuring IFN-gamma and IL-2 expression in absence or presence of CTLA4-Ig by ELISA. RESULTS: Group A patients showed intense tubular staining for B7-1 and B7-2, group B patients showed mild staining, whereas in group C patients B7-1 and B7-2 staining was negative or only weakly positive. In vitro, the presence of B7-1 and B7-2 on PTEC was increased after stimulation with combinations of IL-1alpha, IL-4, IFN-gamma or IL-13 instead of IL-4 and CD40 activation. B7-1 and B7-2 mRNA could be detected in PTEC as well. In MKLCs only cytokine and anti-CD40 prestimulated PTEC were able to stimulate IFN-gamma and IL-2 production by purified T cells, which could be blocked dose-dependently by CTLA4-Ig. CONCLUSIONS: This study clearly shows that B7-1 and B7-2 can be induced on PTEC in vivo and in vitro. After B7-1 and B7-2 induction, PTEC costimulate CD28 on T lymphocytes resulting in cytokine production. This might be of relevance in allograft rejection and in various kidney diseases.